2016
DOI: 10.1093/nar/gkw914
|View full text |Cite
|
Sign up to set email alerts
|

Altered stoichiometryEscherichia coliCascade complexes with shortened CRISPR RNA spacers are capable of interference and primed adaptation

Abstract: The Escherichia coli type I-E CRISPR-Cas system Cascade effector is a multisubunit complex that binds CRISPR RNA (crRNA). Through its 32-nucleotide spacer sequence, Cascade-bound crRNA recognizes protospacers in foreign DNA, causing its destruction during CRISPR interference or acquisition of additional spacers in CRISPR array during primed CRISPR adaptation. Within Cascade, the crRNA spacer interacts with a hexamer of Cas7 subunits. We show that crRNAs with a spacer length reduced to 14 nucleotides cause prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 40 publications
1
49
1
Order By: Relevance
“…We also found that different lengths of crRNAs corresponded to different numbers of backbone (Csm3) and belly (Csm2) subunits in the complex, consistent with the idea that these subunits assemble along the length of the crRNA. The length of Type I Cascade complexes can also be altered by changing the length of the crRNA, suggesting a conserved mechanism for regulation of complex stoichiometry between Type I and III systems [3739]. …”
Section: Discussionmentioning
confidence: 99%
“…We also found that different lengths of crRNAs corresponded to different numbers of backbone (Csm3) and belly (Csm2) subunits in the complex, consistent with the idea that these subunits assemble along the length of the crRNA. The length of Type I Cascade complexes can also be altered by changing the length of the crRNA, suggesting a conserved mechanism for regulation of complex stoichiometry between Type I and III systems [3739]. …”
Section: Discussionmentioning
confidence: 99%
“…Cas9 binding to a beacon results in a readily detectable increase in fluorescence intensity. The rate of fluorescence increase depends on the beacon sequence and structure, which can be varied easily for particular applications (19,20). Schematic representations of the beacon assay and structures of Cas9 beacons 1 and 2 used in this work are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These plasmids were introduced into a strain of E. coli that expresses the full set of type I-E Cas genes required for adaptation and defence (BW40114) 24 . First, we used these strains to see whether any of the cloned plasmid-based NCAs could function in direct interference through a plasmid interference assay 25 by attempting to transform an additional plasmid that also contained the M13 spacer target sequence into cultures expressing the NCA and Cas proteins. If the NCAs are functional, they should reduce the efficiency of this transformation relative to a negative-control plasmid that does not contain a matching protospacer target.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was shown that a more sensitive in vivo test of crRNA function is a primed acquisition assay 25 . Briefly, ‘priming’ is the efficient acquisition of new spacers during a phage challenge of this system stimulated by a pre-existing spacer matching the phage genome that enhances the acquisition of additional phage spacers.…”
Section: Resultsmentioning
confidence: 99%